1993
DOI: 10.1180/minmag.1993.057.389.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chlorine on the crystal structure of a chlorine-rich hastingsite

Abstract: The structure refinement of a hastingsite (Cl 0.91 p.f.u.) from West Ongul Island, Ltitzow-Holm Bay, East Antarctica, has been carried out in order to characterise the effect of CI on the crystal structure.The composition of the Cl-rich hastingsite is Ko 69Nao 26Cal 99Mgl 09Fe2+2 71Fe3+0 92Mn0.~4Ti0 10-A12.31Sis.s3022OH0.99C10.91F0.10 with unit cell parameters a 9.962(3), b 18.283i7), c 5.572(1) )~ and [3 104.87(3) ~ .In the Cl-rich hastingsite, A1, Fe 3 § and Ti occupy only the M(2) site, and Fe 2 § strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…The relationship between chlorine contents and bulk-amphibole composition for the potassium-rich calcic amphiboles is illustrated in Figure 2. There is a slight tendency for Cl content to increase with increasing IV Al and total Fe, comparable to trends observed by others (Makino et al 1993, Morrison 1991, Oberti et al 1993, Volfinger et al 1985.…”
Section: Potassium-rich Amphiboles Associated With Alkali-chloride Mesupporting
confidence: 89%
See 1 more Smart Citation
“…The relationship between chlorine contents and bulk-amphibole composition for the potassium-rich calcic amphiboles is illustrated in Figure 2. There is a slight tendency for Cl content to increase with increasing IV Al and total Fe, comparable to trends observed by others (Makino et al 1993, Morrison 1991, Oberti et al 1993, Volfinger et al 1985.…”
Section: Potassium-rich Amphiboles Associated With Alkali-chloride Mesupporting
confidence: 89%
“…Examples from ), derived from the contents of the B and C sites. Data compiled from Deer et al (1997), with additional compositions taken from Dick & Robinson (1979), Enami et al (1992), Gulyaeva et al (1986), Jiang et al (1994), Kamineni et al (1982), Kullerud (1996), Kullerud & Erambert (1999), Makino et al (1993), Matsubara & Motoyoshi (1985), Mazdab (2001), Mazdab & Barton (2001), Morrison (1991), Oen & Lustenhouwer (1992), Sato et al (1997), Shiraishi et al (1994) and Suwa et al (1987). 15-40, 15-41, 16-1, 16-2 and 16-4.…”
Section: Potassium-rich Amphiboles In Metacarbonatesmentioning
confidence: 99%
“…Figure 2 summarizes the relationships among K, [4] Al and Cl of K -rich (≥0.25 apfu) calcic amphiboles with [4] Al ≥ 1.5 apfu and [A] (Na + K) ≥ 0.5 apfu in this study and from the literature. Figure 2a shows Makino et al (1993) and Oberti et al (1993). Figure 2c clearly shows that K -rich and Cl -poor (less than 1.0 wt% Cl) calcic amphiboles extend their compositional range towards lower X Fe 2+ than K -and Cl -rich calcic amphiboles shown in Figure 2a.…”
Section: Disucussionmentioning
confidence: 75%
“…Bond -valence sums weighted on the occupancies for potassic -ferropargasite control on Cl content in calcic amphibole has been discussed by many authors (e.g., Suwa et al, 1987;Morrison 1991;Enami et al, 1992;Sato et al, 1997). Makino et al (1993) and Oberti et al (1993) revealed the crystal structures of Cl -and K -rich hastingsite and ferropargasite. Based on crystal structure consideration on these amphiboles, they concluded that increasing Cl content in calcic amphiboles crystallochemically requires increasing Fe 2+ , K and [4] Al.…”
Section: Disucussionmentioning
confidence: 99%
“…The variations in halogen contents are principally controlled by the activity of Cl and F in the fluid/melt with which the amphibole and biotite last equilibrated as advocated by many (e.g., Kullerud & Erambert, ; Makino, Tomita, & Suwa, ; Oberti et al, ; Vanko, ; Zhang et al, ). The unusual variably Cl‐enriched amphiboles in the studied intrusions have the highest Cl contents ever reported in the literature for A‐type granites (Bonin & Tatu, ).…”
Section: Discussionmentioning
confidence: 99%